Challenges in Speaking Skills Learning at MTs. NU Durung Bedug Candi - Ariyadi, Firman; Novita, Dian (Inquest Journal, 2024)
This study investigates the challenges faced by VIII grade students in English speaking at a secondary school in Indonesia. Employing observation and interviews, the research identified issues such as limited vocabulary, pronunciation difficulties, and lack of confidence as primary obstacles. The findings underscore the need for educators to diagnose and address these challenges systematically through targeted speaking support and training interventions, aiming to enhance students' proficiency and confidence in spoken English.